INVESTIGAÇÃO DOS EFEITOS CAUSADOS PELA REDUÇÃO DO VOLUME DE DESCARGA - Valencio, Isabella; Gonçalves, Orestes Marraccini (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The current water deficiency has led the population to reduce the water consumption through changing habits and replacing the conventional sanitary appliances for those watersaving. However, this reduction may have negative effects on the performance of the drainage and sewage systems, making it difficult to transport solids and causing pipe blockages. The main objective is to evaluate the impact of reducing toilet water consumption from 6.8Lpf to 4.8Lpf on the performance of the sewage system. In the laboratory study, 260 tests were performed in twenty different toilets. It was clear that simple reduction of the flush tank water level isn't a viable solution to reduce toilet water consumption. In the field study, the monitoring of the water consumption and videos of the sewage system were conducted during eight months in ten houses. When the 6.8Lpf toilets were installed, the average toilet water consumption was 16.6liters/inhabitant/day. When the 4.8Lpf toilets were installed, this value increased to 17.6liters/inhabitant/day. This indicates that the users gave successive flushes. The videos showed blockages in the sewage system. Thus, it isn't possible to conclude that the replacement of the toilets has a major impact on water consumption nor positive effects on the performance of sewage systems.